Preserving Right Pre-motor and Posterior Prefrontal Cortices Contribute to Maintaining Overall Basic Emotion - Nakajima, Riho; Kinoshita, Masashi; Okita, Hirokazu; Liu, Zhanwen; Nakada, Mitsutoshi (Frontiers in Human Neuroscience, 2021)
Basic emotions such as happiness, sadness, and anger are universal, regardless of the human species, and are governed by specific brain regions. A recent report revealed that mentalizing, which is the ability to estimate other individuals’ emotional states via facial expressions, can be preserved with the help of awake surgery. However, it is still questionable whether we can maintain the ability to understand others’ emotions by preserving the positive mapping sites of intraoperative assessment. Here, we demonstrated the cortical regions related to basic emotions via awake surgery for patients with frontal glioma and investigated the usefulness of functional mapping in preserving basic emotion. Of the 56 consecutive patients with right cerebral hemispheric glioma who underwent awake surgery at our hospital, intraoperative assessment of basic emotion could be successfully performed in 22 patients with frontal glioma and were included in our study. During surgery, positive responses were found in 18 points in 12 patients (54.5%). Of these, 15 points from 11 patients were found at the cortical level, mainly the premotor and posterior part of the prefrontal cortices. Then, we focused on cortical 15 positive mappings with 40 stimulations and investigated the types of emotions that showed errors by every stimulation. There was no specific rule for the region-emotional type, which was beyond our expectations. In the postoperative acute phase, the test score of basic emotion declined in nine patients, and of these, it decreased under the cutoff value (Z-score ≤ -1.65) in three patients. Although the total score declined significantly just after surgery (p=0.022), it recovered within 3 months postoperatively. Our study revealed that through direct electrical stimulation, the premotor and posterior part of the prefrontal cortices are related to various kinds of basic emotion, but not a single one. When the region with positive mapping site is preserved during operation, basic emotion function might be maintained although it declines transiently after surgery.